Large Scale characteristics of the galactic HI distribution - Dedes, L. (2005)
sing the new LAB HI survey, a combination of the Leiden/Dwingeloo and the Argentine Surveys processed in Bonn, we study the morphology of the HI distribution in the Milky Way. Assuming circular motions of the gas and hydrodynamical equilibrium we fit a z-density distribution law to extract scale height zh, deviation from the plane ẑ and peak density n̂ . We find that the galactic disk flares from 0.3 kpc at R=9 kpc up to 1 kpc at R=30 kpc without discernable dependence on azimuth. The warp of the galactic disk is also clearly visible, with a symmetric part up to R=17 kpc where the deviation reaches a maximum of 1 kpc, and an asymmetric part where in quadrants 1&2 the deviation reaches a maximum of more than 5kpc at R=28 kpc while in quadrants 3&4 the deviation from the plane drops back to zero. Finally we discuss spiral structure in the peak density plots. Applying the linear density-wave theory we try to model the spiral structure of the Galaxy.